UPAYA PENINGKATAN INVESTASI INDONESIA DI MYANMAR MELALUI DIPLOMASI EKONOMI PASCA DEMOKRATISASI MYANMAR (2011-2013) - Patricia, Ruth Mona; Sushanti, Sukma; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
ABSTRACT This research is attempting to describe the Indonesia’s economic diplomacy to Myanmar after Myanmar’s democratic transition, in an effort to increase Indonesia’s investment in Myanmar. This qualitative-descriptive research uses the concept of democratization, economic diplomacy, and foreign direct investment (FDI) in explicating the research’s result. The initiation of Indonesia’s investment in Myanmar was based on the close bilateral relationship between the two countries, especially during the time when Myanmar was transitioning into a democratic country in 2011. Indonesia, through its BUMN, conducts various economic diplomacy efforts to invest in Myanmar including work visits, assessment of cooperation, permit or proposal application, administrative management, tender, MoU draft discussion, correspondence cooperation, direct observation on Myanmar’s market, and many others. However, not all of the efforts run smoothly; many obstacles must be overcome. Indonesia’s economic diplomacy efforts between 2011-2013 have increased Indonesian investment value in Myanmar from US$ 241,3million to US$ 600 million. Keywords: Economic Diplomacy, Foreign Direct Investment, Democratization